Method for rapid high-temperature phase ceramization of wood surface under open condition and atmospheric environment
The method addresses the challenge of high-temperature ceramicization on wood by forming a composite ceramic layer under open atmospheric conditions, enabling cost-effective and scalable industrial production.
Patent Information
- Application Number
- CN202411276154.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-31
AI Technical Summary
Existing methods for forming high-temperature ceramics on wood surfaces require high temperatures and vacuum conditions, limiting their scalability and cost-effectiveness for industrial applications.
A method for rapid high-temperature ceramicization of wood surfaces under open atmospheric conditions using a combination of carbonization, application of silicone oil and conductive glue, and application of alumina particles in an acidic medium, followed by low-temperature sintering to form a composite ceramic layer.
Enables the formation of a high-temperature composite ceramic layer on wood surfaces at low cost and under open conditions, facilitating industrial-scale production with simple equipment and processes.
Smart Images

Figure CN119217490A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fireproofing of building materials, and in particular to a method for rapid high-temperature phase ceramicization of wood surfaces under open conditions and atmospheric environments. Background Art
[0002] Wood remains a sustainable building material widely used in the construction industry.
[0003] Research shows that one cubic meter of cross-laminated timber (CLT) (CLT is laminated wood panels that are stacked together like building blocks and glued together for stability.) can save about one ton of carbon dioxide. Researchers at the University of Washington found that CLT buildings use 26.5% less energy than their concrete equivalents, from resource extraction to construction. As a natural thermal insulator, wood performs 15 times better than concrete and 400 times better than steel, so buildings require less energy to operate. The engineered wood frames used in the same construction are also 30% lighter than equivalent concrete or steel, which means less heavy machinery is required in transportation and on site, helping to speed up completion. Dalston Works, a 10-story mixed-use development in Hackney, London, was built with CLT and used a total of 111 trucks, while concrete would have required 700 trucks to load. Carbon emissions from the construction industry are huge, and its related activities account for 38% of global energy carbon emissions. The concrete industry accounts for 9% of industrial water use each year.
[0005] However, no material is perfect. Steel shrinks, concrete cracks, and wood burns. Therefore, research on the fire resistance of wood as a building material is urgent.
[0006] Usually, the formation and sintering of high-temperature ceramic SiC (silicon carbide) and the sintering of Al2O3 (aluminum oxide) are carried out at high temperature and in vacuum or atmosphere, while the high-temperature silicon carbide or its composite ceramic layer with alumina formed on the wood surface of this patent is formed at low temperature and in a short time (ordinary household resistance wire furnace) under open conditions and atmospheric environment, and at the same time, the negative charge of wood and the positive charge of alumina dilute acid solution are used for permanent adsorption to form a low-temperature sintering to obtain a high-temperature composite ceramic fireproof layer. Therefore, this technology has the prospect of extremely low cost and industrialization, and has the fireproof function of wood. Summary of the invention
[0007] The object of the present invention is to provide a controllable method for rapidly forming high-temperature ceramics on the surface of wood at low cost under open conditions and atmospheric environment, which can be expected to be industrial-scale.
[0008] The present invention is achieved through the following technical solutions:
[0009] A method for rapid high-temperature ceramicization of wood surface under open conditions and atmospheric environment, the steps are as follows:
[0010] (1) After cleaning and drying the wood under open conditions and atmospheric environment, the wood surface is carbonized, and then the whole piece of wood is immersed in a fire retardant for 1-30 minutes, and then the wood surface is heated; silicone oil is applied to the side of the wood to be ceramicized, and the thickness of the silicone oil is 3-5 mm, and then it is dried;
[0011] (2) For the composite ceramic layer, the surface of the alumina particles is mixed in an acidic medium (such as HCl aqueous solution) under open conditions and atmospheric environment, so that AlCl2OH and AlCl(OH)2 dissociate in water to form positively charged colloid particles. The above solution is immersed in the wood surface, and permanent adsorption occurs due to the negative charge of the wood;
[0012] (3) Under open conditions and atmospheric environment, conductive glue is applied to both ends of the wood in step (1-2), and electricity is applied at 400-500° C. for 0.5-1 minute to form a high-temperature ceramic layer or a composite ceramic layer on the surface of the wood.
[0013] In order to further realize the present invention, the following technical solutions may be preferably selected:
[0014] Preferably, in step (1), the whole piece of wood is immersed in a fire retardant for 1-30 minutes under open conditions and atmospheric environment, and then the surface of the wood is heated; silicone oil is applied to the side of the wood to be ceramicized, and the thickness of the silicone oil is 3-5 mm, and then a mixture of phenolic resin and silicon powder is added. In order to ensure the atomic ratio of silicon to carbon, and because the residual carbon rate of phenolic resin is about 70%, the mass ratio of phenolic resin to silicon is 15-20:25-30, and the silicon-carbon molar ratio is ensured by 1-4 times of siliconization, and then drying is carried out.
[0015] Preferably, in step (1), the whole piece of wood is immersed in a fire retardant for 1-30 minutes under open conditions and atmospheric environment, and then the surface of the wood is heated; silicone oil is applied to the side of the wood to be ceramicized, the thickness of the silicone oil applied is 3-5 mm, and then a mixture of phenolic resin and silicon powder is applied, and then dried.
[0016] Preferably, in step (2), a mixture of phenolic resin and silicon powder is added, dried, and then a mixed solution of nano-alumina particles and HCl is injected into the wood surface at a depth of 1-5 mm and maintained for 0.2-2 hours.
[0017] Preferably, the silicone oil in step (1) is polydimethylsiloxane or dihydroxy-terminated polydimethylsiloxane.
[0018] Preferably, in step (1), the silicone oil is ball-milled under the following ball-milling conditions: a rotation speed of 20-38 r / min, tungsten carbide grinding balls, and a temperature of 10-30°C.
[0019] Preferably, the drying condition of step (1) is drying at 80-120° C. for 10-30 minutes.
[0020] Preferably, the preparation method of the conductive adhesive in step (2) is to use silicon carbide, phenolic resin and graphite conductive adhesive as raw materials, mix and grind them into a paste to obtain the conductive adhesive, and the mass ratio of silicon carbide, phenolic resin and graphite conductive adhesive is (0.5-1): (0.5-0.1): (0.3-1).
[0021] Preferably, the mass concentration of HCl in step (2) is 2-20%.
[0022] Preferably, in step (1), the carbonization treatment condition of the wood surface is to heat the surface of the electric furnace to 150-500 degrees and control the carbonization layer to 1-5 mm.
[0023] Through the above technical solution, the beneficial effects of the present invention are:
[0024] The present invention is based on the future demand for fireproof and waterproof timber in construction, and invents a controllable method for self-generated high-temperature ceramicization of the wood surface under open atmospheric conditions, laying a preliminary foundation for the development of future building materials. Usually, the formation and sintering of high-temperature ceramic SiC (silicon carbide) and the sintering of Al2O3 (aluminum oxide) are all carried out at high temperature and in vacuum or atmosphere, while the high-temperature silicon carbide or its composite ceramic layer with alumina is formed on the wood surface of the present invention under open conditions and atmospheric conditions, at low temperature and in a short time (ordinary household resistance wire furnace), and at the same time, the negative charge of the wood and the positive charge of the dilute acid solution of alumina are used for permanent adsorption and low-temperature sintering to obtain a high-temperature composite ceramic fireproof layer. The present invention can be implemented under open conditions and atmospheric environments, with extremely low equipment requirements, not constrained by external conditions, high applicability, simple process, and convenient industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the equipment;
[0026] Figure 2 This is the XRD spectrum of the block wood surface after wood carbonization;
[0027] Figure 3 This is the XRD pattern after the surface is mixed with silicone oil;
[0028] Figure 4 This is the XRD spectrum of ceramics on the wood surface after the flash test; DETAILED DESCRIPTION
[0029] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0030] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of the embodiments. Based on the embodiments of the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.
[0031] Embodiment 1:
[0032] The specific preparation method of outdoor ceramicization of wood surface is as follows:
[0033] like Figure 1-Figure 4 As shown, first, ① the wood is sawed, the sample is cleaned and dried, ② the wood surface is carbonized and treated in an electric furnace to provide carbonaceous materials for wood ceramicization and remove volatile substances contained in the wood. The treatment temperature is to heat the surface of the electric furnace to 150-500 degrees in an open environment, and the carbonization layer is controlled to be 1-5mm; secondly, the whole piece of wood is immersed in a fire retardant (1-30 minutes), and ③ the side of the wood block that needs to be ceramicized is immersed or coated with a mixture of dihydroxy-terminated polydimethylsiloxane silicone oil or polydimethylsiloxane or phenolic resin and silicon powder after high-energy grinding and patted or vacuum pressure immersed in the above high-energy grinding mixture, and then the above samples are dried (10-30 minutes, 80-120 degrees); ④ the surface layer of alumina particles is mixed in an acidic medium (such as HCl aqueous solution) to dissociate AlCl2OH and AlCl(OH)2 in water into AlCl 2+ 、AlCl 2+ and OH - , Al2O3 particles preferentially adsorb AlCl containing aluminum 2+ and AlCl 2+, forming positively charged colloid particles, and immersing the above solution into the surface of the wood. Since the wood is negatively charged, adsorption occurs; ⑤ Finally, apply the homemade conductive glue (3g of silicon carbide, 2g of phenolic resin, and 3g of graphite conductive glue (according to patent application number 201911031917.7, the patent name is a high-temperature conductive glue and its application) at the thickness of the carbonized layer on both ends of the wood, and apply current and voltage in an open atmospheric environment (no inert atmosphere or other atmosphere is required, which is conducive to on-site construction, has low preparation cost, and is not limited by space and size). Under the action of rapidly accumulated Joule heat, a composite material layer (Al2O3-SiC) can be formed on the surface of the wood in 0.1-5 minutes.
[0034] Characteristics of SiC ceramics: Silicon carbide has stable chemical properties, high thermal conductivity, low thermal expansion coefficient and good wear resistance. Silicon carbide has a high hardness, with a Mohs hardness of 9.5, second only to the world's hardest diamond (10), and has excellent thermal conductivity. It is a semiconductor and can resist oxidation at high temperatures. Due to its specific gravity of 3.2g / cm and high sublimation temperature (about 2700℃), silicon carbide is very suitable as a raw material for bearings or high-temperature furnaces. It will not melt under any pressure that can be achieved and has a very low chemical activity. Due to its high thermal conductivity, high breakdown electric field strength and high maximum current density, many people try to use it to replace silicon in the application of semiconductor high-power components. In addition, it has a strong coupling effect with microwave radiation, and its high sublimation point makes it practical for heating metals.
[0035] Characteristics of Al2O3 ceramics: Alumina is an excellent electrical insulator that can resist extremely high currents, and its electrical resistance increases with its purity. The higher the purity of alumina, the higher the resistance. Alumina ceramics have a very high melting point and strong mechanical strength below 1000 degrees. The excellent chemical stability of alumina is the main reason for its high corrosion resistance. Alumina ceramics are widely used in acid-resistant pump impellers, pump bodies, acid-carrying pipeline linings and valves, etc., and in the manufacture of textile wear-resistant parts and knives due to their excellent chemical stability. This is due to their extremely high hardness and wear resistance, the manufacture of spark plugs, can be used in various engines, and the manufacture of high-pressure sodium lamps and infrared detection window materials. Alumina ceramics with an alumina content of more than 95% can be used as excellent electrical insulators. They also have low dielectric loss and are widely used in electronics and electrical appliances. Transparent alumina exhibits good permeability to visible light and infrared rays. Other important applications of alumina ceramics can be seen in sealing rings, medical prostheses, laser tubes, thermocouple tubes, electronic substrates, bulletproof armor, electrical insulators, grinding media and wear parts.
[0036] Embodiment 2:
[0037] Prepare a wood sample of size 3×4×5cm, and clean and dry it. Heat the wood surface to 500 degrees in an electric furnace in an open environment; apply high-energy ground polydimethylsiloxane on the surface and then dry it. Finally, apply homemade conductive glue on both ends of the wood, and then put it on an electric furnace (400-500 degrees), and then at the same time, apply current and voltage in an open environment (the current is determined by the cross-sectional area, and the current density used in this technology is J = 100000A / m 2 , calculate the required current of 5-10A; this technology generally sets the electric field strength to E=10000V / m, the conductive electrode spacing of the prepared sample is 6mm, and the required voltage can be calculated to be 60V), the low-temperature short-time sintering time is 10-60 seconds, and a high-temperature ceramic SiC layer (phase) can be formed on the surface of the wood.
[0038] Embodiment 3:
[0039] The prepared wood sample is 3×3×5cm in size, and the sample is cleaned and dried; the wood is impregnated with flame retardant for 2 hours and then dried. The carbonization of the wood surface is to heat the surface to 500 degrees in an open atmosphere; the surface infiltration treatment is to take the side of the wood block that needs to be ceramicized and put it into dihydroxy-terminated polydimethylsiloxane silicone oil. The silicone oil submerges the wood surface by about 3mm. Then observe the sample. When the silicone oil diffuses to about 5mm, take out the sample and dry it. The siliconization time is 5 minutes. Finally, apply homemade conductive glue to the end of the wood, and then apply current and voltage for 0.5 minutes in an open atmosphere to form a high-temperature SiC ceramic layer (phase) on the wood surface.
[0040] Embodiment 4:
[0041] Prepare a wood sample of size 3×3×5cm, clean and dry the sample; impregnate the wood with flame retardant for 2 hours, and then dry it. The carbonization of the wood surface is to heat the surface to 500 degrees in an open atmosphere; the surface infiltration treatment is to take the side of the wood block that needs to be ceramicized and put it into dihydroxy-terminated polydimethylsiloxane silicone oil, the silicone oil submerges the wood surface by about 3mm, then observe the sample, when the silicone oil diffuses to about 5mm, take out the sample and dry it; then inject a mixture of nano-alumina powder and HCl into the upper 5mm of the wood, the mass fraction of HCl is 2-20%, and the mass fraction of nano-alumina powder in the mixture is 5-30%, finally apply homemade conductive glue to the end of the wood, and then apply current and voltage for 0.5 minutes in an open atmosphere to form a high-temperature SiC-Al2O3 ceramic layer (phase) on the wood surface. Silicon carbide is generated by reaction, and alumina is attracted and adsorbed by positive and negative charges.
[0042] The data of the sample surface before and after carbonization, and the molar amount of the carbon layer were calculated, see the table below:
[0043]
[0044] The quality data of the sample before and after multiple siliconization are selected to ensure the ideal silicon infiltration molar amount, see the table below:
[0045]
[0046] The molar ratio of silicon to carbon in the wood surface layer, the molar ratio of silicon to carbon obtained satisfies the reaction conditions, see the following table:
[0047]
[0048]
[0049] Table 4-4 Additional current at the end of the wood surface, calculated based on the width and depth of the carbon layer
[0050]
[0051] Finally, it should be noted that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for rapid high-temperature phase ceramicization of wood surface under open conditions and atmospheric environment, characterized in that: Here are the steps: (1) After cleaning and drying the wood in an open atmosphere, carbonize the wood surface, immerse the entire piece of wood in a fire retardant for 1-30 minutes, and then heat the wood surface; apply silicone oil to the side of the wood that needs to be ceramicized, with a thickness of 3-5 mm, and then dry it; (2) For the composite ceramic layer, the surface of the alumina particles is mixed in an acidic medium (such as HCl aqueous solution) under open conditions and atmospheric environment, so that AlCl2OH and AlCl(OH)2 dissociate in water to form positively charged colloid particles. The above solution is immersed in the wood surface, and permanent adsorption occurs due to the negative charge of the wood; (3) Under open conditions and atmospheric environment, conductive glue is applied to both ends of the wood in step (1-2), and electricity is applied at 400-500° C. for 0.5-1 minute to form a high-temperature ceramic layer or a composite ceramic layer on the surface of the wood.
2. The method for rapid high temperature phase ceramicization of wood surface under open conditions and atmospheric environment according to claim 1, characterized in that: In the step (1), the whole piece of wood is immersed in a fire retardant for 1-30 minutes under open conditions and atmospheric environment, and then the surface of the wood is heated; silicone oil is applied to the side of the wood to be ceramicized, and the thickness of the silicone oil is 3-5 mm, and then a mixture of phenolic resin and silicon powder is added. In order to ensure the atomic ratio of silicon to carbon, and because the residual carbon rate of phenolic resin is about 70%, the mass ratio of phenolic resin to silicon is 15-20:25-30, and the silicon-carbon molar ratio is ensured by 1-4 times of siliconization, and then drying is performed.
3. The method for rapid high temperature phase ceramicization of wood surface under open conditions and atmospheric environment according to claim 1, characterized in that: In the step (1), the whole piece of wood is immersed in a fire retardant for 1-30 minutes under open conditions and atmospheric environment, and then the surface of the wood is heated; silicone oil is applied to the side of the wood to be ceramicized, the thickness of the silicone oil applied is 3-5 mm, and then a mixture of phenolic resin and silicon powder is applied, and then dried.
4. The method for rapid high temperature phase ceramicization of wood surface under open conditions and atmospheric environment according to claim 1, characterized in that: In the step (2), a mixture of phenolic resin and silicon powder is patted in and dried, and then a mixed solution of nano-alumina particles and HCl is injected into the wood surface at a depth of 1-5 mm and maintained for 0.2-2 hours.
5. The method for rapid high temperature phase ceramicization of wood surface under open conditions and atmospheric environment according to any one of claims 1 to 3, characterized in that: The silicone oil in step (1) is polydimethylsiloxane or dihydroxy-terminated polydimethylsiloxane.
6. The method for rapid high temperature phase ceramicization of wood surface under open conditions and atmospheric environment according to any one of claims 1 to 3, characterized in that: In the step (1), the silicone oil is ball-milled under the following ball-milling conditions: a rotation speed of 20-38 r / min, tungsten carbide grinding balls, and a temperature of 10-30°C.
7. A method for rapid high temperature phase ceramicization of wood surface under open conditions and atmospheric environment according to any one of claims 1 to 3, characterized in that: The drying condition of step (1) is drying at 80-120° C. for 10-30 minutes.
8. The method for rapid high temperature phase ceramicization of wood surface under open conditions and atmospheric environment according to claim 1, characterized in that: The preparation method of the conductive adhesive in step (2) is to use silicon carbide, phenolic resin and graphite conductive adhesive as raw materials, mix and grind them into a paste to obtain the conductive adhesive, and the mass ratio of silicon carbide, phenolic resin and graphite conductive adhesive is (0.5-1): (0.5-0.1): (0.3-1).
9. The method for rapid high temperature phase ceramicization of wood surface under open conditions and atmospheric environment according to claim 4, characterized in that: The mass concentration of HCl in step (2) is 2-20%.
10. The method for rapid high temperature phase ceramicization of wood surface under open conditions and atmospheric environment according to claim 1, characterized in that: In the step (1), the carbonization treatment condition of the wood surface is to heat the surface of the electric furnace to 150-500 degrees, and control the carbonization layer to 1-5 mm.
